2015
DOI: 10.1177/0022034515577411
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200a Regulates the Development of Mandibular Condylar Cartilage

Abstract: Mandibular condylar cartilage (MCC) is classified as secondary cartilage, the histologic structure of which is unique from that of primary cartilage. MicroRNA (miRNA) is a small noncoding RNA that binds to the messenger RNA (mRNA) target to repress its translation and plays an important role in cell differentiation, proliferation, and death. Microarray analysis revealed that miR-200a was characteristically expressed during embryonic development. We hypothesized that miR-200a may be involved in regulating the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…These miRNAs include miR-16-5p and miR-337, both of which target Smad3 [146] and TGFβR2 [147], respectively. A number of other miRNAs may target SOX9 and COL2A1 in chondrocytes including miR-101 [148], miR-675 [149], and miR-200a [150]. Interestingly, inhibition of these miRNAs may enhance chondrogenesis and have a protective function in OA conditions.…”
Section: Mirna Regulation Of Chondrogenesis and Cartilage Homeostasismentioning
confidence: 99%
“…These miRNAs include miR-16-5p and miR-337, both of which target Smad3 [146] and TGFβR2 [147], respectively. A number of other miRNAs may target SOX9 and COL2A1 in chondrocytes including miR-101 [148], miR-675 [149], and miR-200a [150]. Interestingly, inhibition of these miRNAs may enhance chondrogenesis and have a protective function in OA conditions.…”
Section: Mirna Regulation Of Chondrogenesis and Cartilage Homeostasismentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous, short (~22 nucleotide), noncoding, single‐stranded RNAs that can regulate translational inhibition or mRNA degradation by binding to the 3′ untranslated regions (3′‐UTRs) of some specific mRNAs . Studies have shown that miRNAs participate in a range of pathological and physiological processes, including cell proliferation, differentiation, apoptosis, organ development, and tumor oncogenesis . In particular, numerous studies have published that miRNAs play critical roles in osteogenic differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…Umeda et al identified miR200a as a major regulator of the formation of cartilage during mandibular condylar cartilage (MCC) development. Transfection of antimiR-200a in MCC cells or organ culture positively influenced chondrogenesis, inducing the expression of Sox9 and collagen type II [24].…”
Section: Silencing Of Non-coding Rnasmentioning
confidence: 99%
“…Nevertheless, increasing evidence strongly suggests that the silencing of key anti-chondrogenic regulators may be effectively employed to enhance or even induce chondrogenesis, stimulate the production of cartilage matrix, and improve or stabilize the chondrocytic phenotype [21][22][23][24].…”
Section: Gene Silencing For Chondrogenesis: Potentialities and Challementioning
confidence: 99%
See 1 more Smart Citation